DNA nanotweezers studied with a coarse-grained model of DNA - Ouldridge, T; Louis, A; Doye, J (American Physical Society, 2010)
We introduce a coarse-grained rigid nucleotide model of DNA that reproduces the basic thermodynamics of short strands: duplex hybridization, single-stranded stacking and hairpin formation, and also captures the essential structural properties of DNA: the helical pitch, persistence length and torsional stiffness of double-stranded molecules, as well as the comparative flexibility of unstacked single strands. We apply the model to calculate the detailed free-energy landscape of one full cycle of DNA 'tweezers', a simple machine driven by hybridization and strand displacement.